Towards The Future Of Education: Digital Leadership In Public Junior High Schools In The Northern Region Of Bandung - Pribadi, Luthfi Audia; Zulfikar, Zulfikar; Edy, Sarwo; Permana, Indra (LPPM Universitas PGRI Sumatera Barat, 2025)
This research focuses on the analysis of digital-based educational leadership skills in public middle schools (SMP Negeri) in the northern region of Bandung City, emphasizing the supporting and inhibiting factors of implementation. The study highlights seven main digital-based leadership skills: Digital Attitude, Leadership Ability, Communication Skills, Social Skills, Team Building Skills, Change Management Skills, and Trustworthiness. Through interviews with school principals, the study reveals that leadership in Bandung City public middle schools has adapted to technological advancements, such as using virtual media to communicate school programs and policies and holding online meetings. The research employs a descriptive method with a qualitative approach. Data were obtained through interviews with school principals in public middle schools in Bandung City. Data processing and analysis were conducted using Nvivo 12 software. The qualitative approach allows researchers to gain an in-depth understanding of digital-based leadership skills from the perspective of educational practitioners, while the use of Nvivo 12 helps in efficiently organizing and analyzing the data. The findings indicate that principals in public middle schools in Bandung City have generally demonstrated digital-based leadership skills.